Genetic modifiers of long‐term survival in sickle cell anemia. Issue 4 (12th August 2020) - Wonkam, Ambroise; Chimusa, Emile R.; Mnika, Khuthala; Pule, Gift Dineo; Ngo Bitoungui, Valentina Josiane; Mulder, Nicola; Shriner, Daniel; Rotimi, Charles N.; Adeyemo, Adebowale
Abstract: Background: Sickle cell anemia (SCA) is a clinically heterogeneous, monogenic disorder. Medical care has less‐than‐optimal impact on clinical outcomes in SCA in Africa due to several factors, including patient accessibility, poor access to resources, and non‐availability of specific effective interventions for SCA. Methods: Against this background, we investigated 192 African participants who underwent whole exome sequencing. Participants included 105 SCA patients spanning variable clinical expression: a "long survivor" group (age over 40 years), a "stroke" group (at least one episode of overt stroke), and a "random" group (patients younger than 40 years without overt cerebrovascular disease). Fifty‐eight ethnically matched homozygous hemoglobin A controls were also studied. Findings were validated in an independently recruited sample of 29 SCA patients. Statistical significance of the mutational burden of deleterious and loss‐of‐function variants per gene against a null model was estimated for each group, and gene‐set association tests were conducted to test differences between groups. Results: In the "long survivor" group, deleterious/loss‐of‐function variants were enriched in genes including CLCN6 (a voltage‐dependent chloride channel for which rare deleterious variants have been associated with lower blood pressure) and OGHDL (important in arginine metabolism, which is a therapeutic target in SCA). In the "stroke" group, significant genes implicated were associated with increased activity of the blood coagulation cascade and increased complement activation, for example, SERPINC1, which encodes antithrombin. Oxidative stress and glutamate biosynthesis pathways were enriched in "long survivors" group. Published transcriptomic evidence provides functional support for the role of the identified pathways. Conclusions: This study provides new gene sets that contribute to variability in clinical expression of SCA. Identified genes and pathways suggest new avenues for other interventions. Abstract : This study provides new insights into the pathophysiology of sickle cell anemia (SCA) by identifying gene sets with deleterious/loss‐of‐function variants that contribute to variability in SCA clinical expression. In the "long survivor" group (age over 40 years), enriched genes included CLCN6 (a voltage‐dependent chloride channel for which rare deleterious variants have been associated with lower blood pressure) and OGHDL (important in arginine metabolism, which is a therapeutic target in SCA). In the "stroke" group, enriched genes implicated increased activity of the blood coagulation cascade and increased complement activation; Notable among these genes is SERPINC1 that encodes antithrombin. Identified genes and pathways suggest new avenues for other interventions.